Reasons for seeking dental healthcare services in a Nigerian missionary hospital - Oseremen Gabriel Ogbebor; Clement Chinedu Azodo (Sahel Medical Journal, 2016)
Objective: To determine the reasons for seeking dental healthcare services in a missionary hospital in Benin City, Nigeria. Materials and Methods: This 14-month retrospective study was conducted in a Pentecostal missionary hospital in Benin City. Data of interest which included age, gender, occupation, primary presenting complaints, and primary diagnosis were collected from the case notes with self-designed proforma. Cases with incomplete data were excluded from this study. The obtained data were subjected to descriptive statistics in the form of frequencies, cross tabulations, and percentages using Statistical Package for the Social Sciences version 17.0. Results: A total of 613 cases were retrieved with the complete information. The majority (56.3%) of the patients were young adults (18-40 years). About one-fifth (21.2%) of the patients were middle-aged adults. Children and elderly constituted 15.8% and 6.7% of the patients, respectively. A total of 332 (54.2%) patients were females. There was diversity in the occupation of the patients with about one-third (37.7%) of the patients being students. The majority of the patients had toothache as their primary presenting complaint (71.1%). Others were tooth deposits (6.0%), fractured teeth (3.8%), hole in teeth (3.1%), missing teeth for replacement (2.3%), routine dental check-up (2.3%), and mouth odor (2.0%). Diagnosis of dental caries and its complications was made in more than half (58.6%) of the patients while one-fifth (20.4%) of the patients were diagnosed with gingivitis. Conclusion: Data from this study revealed that these enormous diverse patients of a Nigerian missionary hospital had toothache as their main primary presenting complaint and dental caries and its complication as their main primary diagnosis.